ULTRASONOGRAPHY AND PREGNANCY OUTCOMES IN CASES OF THREATENED ABORTION: A PROSPECTIVE OBSERVATIONAL STUDY - Quadri, Maryam (Student's Journal of Health Research Africa, 2024)
Background Threatened miscarriage, characterized by vaginal bleeding in early pregnancy, is a common complication that can significantly impact maternal and fetal outcomes. The ability to accurately predict pregnancy loss is crucial for effective clinical management. This study aims to evaluate the diagnostic performance of early ultrasound parameters in predicting pregnancy outcomes among women presenting with threatened miscarriage. Methods A prospective observational study was conducted involving 200 patients diagnosed with threatened miscarriage at a tertiary care center. Inclusion criteria included normal body mass index (BMI), a known last menstrual period (LMP), absence of cervical pathology, and a single viable pregnancy. Participants were divided into three groups: Group I (pregnancy loss), Group II (ongoing pregnancy), and Group III (control group). Ultrasound examinations were performed to assess fetal heart rate (FHR), gestational sac diameter (GSD), crown-rump length (CRL), and yolk sac diameter (YSD). Maternal and neonatal outcomes were recorded, and statistical analyses were performed using SPSS 10. Results Among the participants, 30% experienced pregnancy loss (Group I), while 70% continued their pregnancies (Group II). Significant differences were observed in ultrasound parameters, with Group I showing lower FHR (mean 98.2 bpm) and smaller GSD (mean 14.5 mm) compared to Groups II and III. The diagnostic performance of FHR <100 bpm and GSD <15 mm was found to be highly predictive of miscarriage, with sensitivities of 85% and 80%, respectively. Conclusion Early ultrasound parameters, particularly FHR and GSD, are valuable indicators of pregnancy outcomes in cases of threatened miscarriage. Their predictive capabilities can guide clinical management, allowing for closer monitoring and tailored interventions. Recommendations It is recommended that clinicians utilize early ultrasound assessments in women presenting with threatened miscarriages to improve pregnancy outcomes. Further studies are needed to validate these findings and explore additional markers that may enhance predictive accuracy.